Lead-free high curie point PTC ceramic material and preparation method thereof

Through weak oxidation and low oxygen partial pressure sintering process, in the preparation of lead-free high Curie temperature PTC ceramic materials, the problem of difficult to obtain both low room temperature resistance, lift-resistance ratio and resistance temperature coefficient in the prior art is solved, and the integration of materials is achieved Performance improvement and process simplification are suitable for market applications.

CN119191836APending Publication Date: 2024-12-27SHANGHAI INST OF SPACE PROPULSION +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411201129.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lead-free high Curie temperature PTC ceramic materials have problems in the preparation process that low room temperature resistance, lift-resistance ratio and resistance temperature coefficient are difficult to obtain, and the process is complex and unstable, which cannot meet market demand.

Method used

Were weak oxidation and low oxygen partial pressure sintering process to simultaneously realize material semiconductor and grain boundary barrier construction in one process, reduce the process flow, and improve the repetition and pass rate of material preparation.

Benefits of technology

The coordinated regulation of low room temperature resistance, high lift-resistance ratio and high resistance temperature coefficient is achieved, and the comprehensive performance of PTC materials is obtained, which is suitable for practical production and manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191836A_ABST
    Figure CN119191836A_ABST
Patent Text Reader

Abstract

The invention relates to a lead-free high curie point PTC ceramic material and a preparation method thereof, the lead-free high curie point PTC ceramic material is sintered in a quantitative weak oxidation low oxygen partial pressure atmosphere, grain semiconduction and grain boundary potential barrier construction are integrated in the same process, a subsequent oxidation treatment process is not needed, the process flow is shortened, and the material preparation repeatability is improved. The prepared PTC ceramic material does not contain lead element, has a high Curie temperature point of 150-195 DEG C, a high lift-drag ratio of 3-6, a low room temperature resistance of 10-1000 ohm and a high resistance temperature coefficient of more than or equal to 30% / DEG C, has excellent comprehensive performance, is suitable for practical production and manufacturing, and has high market application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic ceramic materials, and in particular relates to a lead-free high Curie temperature PTC ceramic material and a preparation method thereof. Background Art

[0002] PTC ceramic material is a semi-conductive ferroelectric ceramic, which shows a step-like increase in resistance due to phase change above the Curie temperature. PTC ceramic material can be used in constant temperature heating, overcurrent and overheat protection, temperature sensing and other related electronic components due to its resistance-temperature, voltage-current, current-time and other characteristics.

[0003] In the traditional applications of PTC materials, air-conditioning heaters, automobile manifold heaters, curling irons, and constant temperature heating elements occupy a large market share, and all use PTC materials with a Curie temperature Tc higher than 150°C. In emerging application areas, such as thermal battery overheating protection and high-voltage power and high-current protection, more PTC materials with Tc ≥ 180°C will be required to achieve automatic protection of the circuit under overheating conditions. However, the current commercial high Curie temperature point PTC materials are usually adjusted by adding a peak shifter containing Pb, which will cause pollution to the environment. Chinese invention patent CN104844196B discloses a high Curie temperature PTC ceramic material. Although the formula design reduces the sintering temperature and suppresses the volatilization of Pb to a certain extent, the material system still contains lead, and there is a risk of pollution under specific conditions.

[0004] With the release of the EU lead ban in 2006, electronic materials are required to be environmentally friendly. Research on lead-free PTC ceramic materials has been carried out at home and abroad. The relatively mature material systems currently studied include ZnO-NiO-TiO2 system, BaTiO3-Bi 0.5 Na 0.5 TiO3 system and ZnO-NiO-TiO2 system usually have higher room temperature resistance (10 4 -10 6 Ω), low lift-to-drag ratio (1-2), and easy aging. 0.5 Na 0.5 TiO3 system is highly doped with Bi 0.5 Na 0.5 TiO3 (molar percentage ≥ 4%) cannot be sintered and semi-conducted in air atmosphere, so most of them adopt the process of first reduction and then oxidation. The ceramic resistor prepared in reducing atmosphere is small (10 -1-10Ω), the lift-to-drag ratio is not high (1-2), and the temperature coefficient of resistance is also small (≤10% / ℃). The literature Jifeng Wei, Yongping Pu, J Mater Sci: Mater electron (2011) 22: 551-554 mentioned that heat treatment and reoxidation of PTC ceramics prepared in a reducing atmosphere at a specified temperature will cause a significant increase in room temperature resistance (≥10 3 Ω), which is not conducive to practical application, nor to the improvement of the comprehensive performance of PTC materials, and the reduction and reoxidation process increases the complexity of the process. 0.5 Na 0.5 While TiO3 has a high Curie temperature, the lead-free PTC material still has low room temperature resistance, high rise-to-resistance ratio and high temperature coefficient of resistance, which is the key to achieving BT-Bi 0.5 Na 0.5 The key technical breakthrough point for the practical application of TiO3 system lead-free PTC ceramic materials.

[0005] Chinese invention patent CN116332639A discloses a method of reduction and reoxidation step-by-step sintering to prepare lead-free high Curie temperature PTC ceramics. First, semiconducting PTC ceramics are prepared in a reducing atmosphere of CO:N2=1:4, and then reoxidized in air at 800-1060°C. The Curie temperature of the obtained PTC ceramics can reach 150-180°C, and the lift-to-drag ratio lg (Rmax / Rmin) is increased to 5 orders of magnitude. The patent completes the preparation of PTC ceramics in two steps of sintering and reoxidation, and the oxygen content in the air of the reoxidation process of different batches of samples is not consistent. In the actual production process, there will be many steps, poor repeatability of PTC material performance, and low stability; and there is no mention of optimizing the resistance temperature coefficient of ceramic materials.

[0006] In the existing preparation process, the atmosphere semiconducting regulates the carrier concentration in the PTC material system to achieve a lower resistance value for the PTC material, but it is not conducive to the formation of grain boundary barriers in the PTC polycrystalline material system, resulting in a low resistance-to-resistance ratio; after the reoxidation process, the grain boundary barriers are reconstructed to increase the resistance-to-resistance ratio, but at the same time, the oxygen vacancies are filled, and the carrier concentration is reduced, resulting in an increase in room temperature resistance. It is impossible to achieve the coordinated regulation of low room temperature resistance, high resistance-to-resistance ratio and high resistance temperature coefficient, and the prepared PTC ceramic material has poor comprehensive performance. Chinese invention patent CN104030679B discloses a method for preparing lead-free PTC ceramics under a reducing atmosphere, firstly, the PTC material is semiconducted in a reducing atmosphere N2, and then the CuO valence change characteristics in the material system are used to achieve the establishment of a new barrier, but the large amount of CuO enriched at the grain boundary makes the room temperature resistance of the sintered PTC material all below 10 3 Ω or more, lift-to-drag ratio lg(Rmax / R min )≤3, Curie temperature T c ≤140℃, the comprehensive performance needs to be further optimized, but it still cannot meet the practical needs of most markets. Chinese invention patent CN102745987B discloses a method for obtaining lead-free high Curie temperature PTC ceramic materials by sintering at room temperature, mainly by doping Na2Ti6O 13 The Curie temperature was raised and the material was semiconducted, and the Curie temperature T c The room temperature resistance of the prepared PTC material is relatively large, both at 10 3 However, in actual low-voltage application scenarios, PTC ceramics are usually required to have a lower resistance.

[0007] The prior patent CN104370539 discloses a preparation process using a nitrogen one-step sintering method, and turns off the nitrogen during the cooling process after sintering, so that oxygen in the air has the opportunity to enter the sample, and the adsorption of oxygen at the grain boundary produces a barrier height. Its essence is still sintering in a reducing nitrogen environment, and then performing a reoxidation process, that is, two processes are performed separately, reduction and reoxidation processes. The material finally obtained has a lift-to-drag ratio of 2-5 orders of magnitude; resistance temperature coefficient: 10-20% / ℃. It is divided into two processes for preparation, especially by turning off the nitrogen to allow the oxygen in the air to reoxidize the PTC ceramics randomly, and the resistance temperature coefficient obtained is not very high. And whether the oxygen in the air can enter the sample as expected after turning off the nitrogen has a large uncertainty, and the repeatability of the obtained sample will also be affected, which will lead to a high failure rate in actual scientific research and production, and the practicality is not high. Summary of the invention

[0008] The object of the present invention is to provide a kind of 3 The lead-free high Curie temperature (150-195°C) PTC ceramic material has high Ω), high lift-to-resistance ratio (3-6) and high temperature coefficient of resistance (≥30% / °C). The raw materials used in its preparation do not contain lead, and it has no pollution to the environment. The preparation process is simple, and the semi-conductivity of the grains and the construction of the grain boundary barrier can be completed in one sintering process, without the need for post-processing and re-oxidation process.

[0009] In the prior art, sintering is directly carried out in a reducing atmosphere. In the reducing atmosphere, more oxygen vacancies will be generated in the ceramic body as conductive carriers, thereby realizing the semiconductivity of the material. However, the reducing atmosphere is not conducive to the establishment of grain boundary barriers. Sintering using this process only semiconducts the material without constructing the grain boundary barriers. The prepared PTC ceramics usually have a very low lift-to-drag ratio. In order to rebuild the grain boundary barriers, a reoxidation process is usually used to supplement the oxygen at the grain boundaries on the basis of realizing the reduction and semiconductivity of the material, increase the acceptor state density and thus improve the grain boundary barriers. Reduction (semiconductivity) and reoxidation (grain boundary barrier construction) are separated into two independent processes. The present invention is sintered in a weakly oxidizing low oxygen partial pressure atmosphere, which appropriately increases the oxygen vacancies in the material system to facilitate the semiconductivity of the material, while ensuring that there is a certain amount of oxygen on the grain boundaries to form surface acceptor states. The semiconductivity of the material and the construction of the grain boundary barriers are carried out simultaneously in one process, ensuring that the lift-to-drag ratio is improved while the material has low resistance.

[0010] The main idea of ​​the present invention is to quantitatively and accurately control the weakly oxidizing and low oxygen partial pressure sintering atmosphere so that the atmosphere semiconducting and reoxidation processes (barrier construction process) in the preparation process of high Curie temperature PTC materials are concentrated in the same sintering process, which can simultaneously realize the coordinated regulation of grain resistance and grain boundary barriers, shorten the process flow, and quantify the sintering process atmosphere parameters, thereby improving the repeatability of material preparation and the qualified rate in the production process, which is more conducive to the coordinated regulation of PTC material performance parameters and the improvement of the comprehensive performance of materials, is closer to practical needs, and has a higher market application value.

[0011] The objective of the present invention is achieved through the following technical solutions:

[0012] <First aspect>

[0013] The invention provides a method for preparing a lead-free high Curie point PTC ceramic material, comprising: sintering the lead-free high Curie point PTC ceramic material to be sintered in a weakly oxidizing low oxygen partial pressure atmosphere to obtain the lead-free high Curie point PTC ceramic material.

[0014] As an embodiment of the present invention, the oxygen partial pressure in the weakly oxidizing low oxygen partial pressure atmosphere is 40-700 ppm.

[0015] As an embodiment of the present invention, the sintering of the lead-free high Curie point PTC ceramic material to be sintered in a weakly oxidizing low oxygen partial pressure atmosphere specifically comprises the following steps:

[0016] The lead-free high Curie point PTC ceramic material to be sintered is placed in an atmosphere furnace body, and gas is introduced to form a weakly oxidizing low oxygen partial pressure atmosphere. The gas flow rate and the oxygen partial pressure of the furnace body are precisely controlled (by the mass flow controller MFC). The temperature is raised to 1240-1360°C and kept for 0.5-2h for sintering, and then the temperature is cooled to room temperature at a rate of 2-4°C / min to obtain the lead-free high Curie point PTC ceramic material.

[0017] As an embodiment of the present invention, the preparation method further comprises:

[0018] S1. Ingredients: prepare base material and auxiliary materials. The base material is BaTiO3 75-95% and Bi 0.5 Na 0.5 TiO3 5-25% is weighted, and the auxiliary materials are weighted according to the total mass percentage of TiO2 0.5-1.5%, Al2O3 0.05-0.25%, SiO2 0.5-2.5%, MnCO3 0.05-0.5%, Nb2O5 0.1%-0.3%, Y2O3 0.3-1.5%, and CeO2 0.5-1.5% mixed with the base material;

[0019] S2, PTC raw material mixing and pre-calcining: the prepared materials in S1 are mixed with anhydrous ethanol and then (planetary) ball milled, dried and sieved after ball milling, pre-calcined, and crushed after cooling to room temperature;

[0020] S3, preparing PTC green billet: adding 5-8% of the dry powder weight of organic binder to the pre-calcined and crushed PTC powder for granulation, sieving again, and molding into green billet;

[0021] S4. Debinding of PTC green billet: Debinding the green billet (placed in a high-temperature electric furnace) to obtain a lead-free high Curie point PTC ceramic material to be sintered.

[0022] As an embodiment of the present invention, the BaTiO3 in step S1 is prepared by a hydrothermal method, the preparation method comprising: 16 H 36 O4Ti and barium nitrate Ba(NO3)2 are dissolved in deionized water in a molar ratio of (0.95-1.05):1, stirred and (ultrasonic) mixed evenly, and then transferred to a reaction kettle, sealed and kept at 400-500℃ for 10-16h, cooled to room temperature, filtered, washed, dried, and sieved to obtain. The sieve mesh is 40 mesh.

[0023] As an embodiment of the present invention, Bi in step S1 0.5 Na 0.5TiO3 is prepared by a solid phase method, and the preparation method includes: mixing Na2O3, Bi2O3 and TiO2 in a molar ratio of 1:1:4 and (placing in a planetary ball mill) mixing evenly, and then (placing in a crucible) (in a high temperature electric furnace) 1100-1200℃ for 1.5-3h synthesis, sieving 40 mesh for use. When mixing planetary ball milling, the material: ball: anhydrous ethanol = 1: (2.5-3.5): (1.5-3), the ball milling speed is 350-550r / min, the ball milling time is 4-6 hours, and the drying temperature after ball milling is 80℃-90℃.

[0024] As an embodiment of the present invention, during ball milling in step S2, the mass ratio of material: ball: anhydrous ethanol is 1: (2.5-3.5): (1.5-3), the ball milling speed is 350-550 r / min, and the ball milling time is 4-6 h.

[0025] As an embodiment of the present invention, the pre-calcination in step S2 is performed at 800-950° C. (in a high temperature electric furnace) for 1-2 hours.

[0026] As an embodiment of the present invention, the organic binder in step S3 is a polyvinyl alcohol solution.

[0027] Specifically, the mass fraction of the polyvinyl alcohol solution is 6 wt.%.

[0028] As an embodiment of the present invention, the molding in step S3 is carried out under a flat vulcanizing press, and the pressure during molding is 1-1.5T / cm 2 , and maintain the pressure at this pressure for 1-3 minutes.

[0029] As an embodiment of the present invention, in step S4, the green blank (placed in a high-temperature electric furnace) is kept at 500-800° C. for 1.5-3 hours for debinding.

[0030] As a specific embodiment of the present invention, the preparation method of the lead-free high Curie point PTC ceramic material specifically comprises the following steps:

[0031] (1)Bi 0.5 Na 0.5 Synthesis of TiO3: Mix Na2O3, Bi2O3 and TiO2 in a molar ratio of 1:1:4 in a planetary ball mill, mix them evenly, then place them in a crucible for synthesis, and sieve through 40 mesh for later use;

[0032] During the mixed planetary ball milling, the material: ball: anhydrous ethanol = 1: (2.5-3.5): (1.5-3), the ball milling speed is 350-550r / min, the ball milling time is 4-6 hours, and the drying temperature after ball milling is 80℃-90℃; the synthesis temperature in the crucible is 1100-1200℃, and the synthesis time is 1.5-3h to obtain Bi0.5 Na 0.5 TiO3;

[0033] (2) Synthesis of BaTiO3: Tetrabutyl titanate C 16 H 36 O4Ti and barium nitrate Ba(NO3)2 are dissolved in deionized water in a molar ratio of (0.95-1.05):1, stirred and ultrasonically homogenized, and then transferred to a reaction kettle, sealed and kept at 400-500℃ for 10-16h, cooled to room temperature, filtered, washed, dried, and sieved through 40 mesh for later use, to obtain BaTiO3;

[0034] (3) PTC raw material mixing and pre-sintering: the base material is BaTiO3 75-95% and Bi 0.5 Na 0.5 TiO35-25% is used as the weight, and the auxiliary materials are weighted according to the total mass percentage of TiO2 0.5-1.5%, Al2O3 0.05-0.25%, SiO20.5-2.5%, MnCO3 0.05-0.5%, Nb2O5 0.1%-0.3%, Y2O3 0.3-1.5%, and CeO2 0.5-1.5% mixed with anhydrous ethanol and then planetary ball milled, the mass ratio of material: ball: anhydrous ethanol is 1: (2.5-3.5): (1.5-3), the ball milling speed is 350-550r / min, after ball milling for 4-6h, it is dried, sieved with 40 mesh, placed in a crucible, pre-calcined at 800-950℃ for 1-2h, and crushed after cooling to room temperature;

[0035] (4) Preparation of PTC green billet: Add 5-8% of the dry powder weight of organic binder (6wt.% polyvinyl alcohol solution) to the pre-calcined and crushed PTC powder for granulation, and sieve through 40 mesh again; then mold it under a flat vulcanizer with a pressure of 1-1.5T / cm 2 , keep the pressure for 1-3min to form a green billet with a size of Φ13mm*5mm;

[0036] (5) PTC green billet debinding: The green billet is placed in a high-temperature electric furnace for debinding to remove the organic binder added during the granulation process. The debinding process conditions are preferably 500-800°C for 1.5-3h;

[0037] (6) Adjusting the sintering atmosphere: placing the debinded green blank (i.e., the lead-free high Curie point PTC ceramic material to be sintered) in the atmosphere furnace, and introducing gas to accurately control the gas flow rate through the mass flow controller MFC until the oxygen partial pressure in the furnace is 40-700 ppm;

[0038] (7) Heating and sintering: heating to 1240-1360°C and keeping the temperature for 0.5-2h, sintering, and cooling to obtain the desired PTC ceramic sheet;

[0039] (8) Coating an electrode on the surface of the PTC ceramic sheet obtained above, and performing a resistance-temperature curve test on the ceramic sheet after the electrode coating; the electrode is preferably selected from one of a silver electrode, an aluminum electrode, and a titanium electrode.

[0040] As one embodiment of the present invention, the weakly oxidizing low oxygen partial pressure atmosphere is obtained by introducing an oxidizing gas into an inert gas or a reducing gas; or, by consuming part of the oxygen in the oxidizing gas.

[0041] Specifically, when a weakly oxidizing low oxygen partial pressure atmosphere is obtained by consuming part of the oxygen in the oxidizing gas, the substance consuming oxygen is preferably one of carbon powder and phosphorus powder.

[0042] As an embodiment of the present invention, the inert gas includes one or more of argon, helium, and neon; the reducing gas includes one or more of hydrogen, nitrogen, ammonia, and carbon monoxide; and the oxidizing gas includes one or more of oxygen, air, ozone, and carbon dioxide.

[0043] As one embodiment of the present invention, the above-mentioned gases themselves can be used to obtain a weakly oxidizing low oxygen partial pressure atmosphere; alternatively, chemical substances that can form these gases through synthesis or decomposition reactions can be added to form a weakly oxidizing low oxygen partial pressure atmosphere.

[0044] <Second Aspect>

[0045] The present invention provides a lead-free high Curie point PTC ceramic material, which is prepared by any of the methods described above. The Curie temperature T c 150-195℃, lift-to-drag ratio lg(R max / R min ) is 3-6, room temperature resistance R 25 The resistance is 10-1000Ω, and the resistance temperature coefficient α is ≥30% / ℃.

[0046] In some specific embodiments, the Curie temperature Tc of the prepared PTC ceramic material is 150-195°C, the rise-to-resistance ratio lg (Rmax / Rmin) is 3-6, the room temperature resistance R25 is 100-600Ω, and the resistance temperature coefficient α is ≥30% / °C.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] (1) Reduce the process flow, improve the repetition rate of material preparation, and reduce process instability; the present invention innovatively adopts precise quantitative control of the low oxygen pressure weak oxidation environment of the sintering furnace body, and concentrates the semiconductivity of the lead-free high Curie temperature point PTC ceramic grains and the construction of grain boundary barriers in one sintering process, which saves the process flow and provides a new method for the preparation of high Curie point lead-free PTC ceramic materials; in addition, the process sintering atmosphere is precisely quantified, which reduces the uncertainty in the process of the existing technology;

[0049] (2) The problem that it is difficult to achieve both low PTC resistance and high lift-to-resistance ratio and high resistance temperature coefficient in the preparation process of high Curie temperature PTC ceramic materials is improved, and a more excellent comprehensive performance of PTC materials is obtained, which is more suitable for practical production and manufacturing and has a higher market application value; the PTC ceramic material prepared by sintering in a single process under a specific weak oxidation and low oxygen partial pressure adopted in the present invention realizes the coordinated regulation and synchronous improvement of the performance of PTC ceramic materials, wherein the Curie temperature T c 150-195℃, lift-to-drag ratio lg(R max / R min ) is 3-6, room temperature resistance R 25 The resistance temperature coefficient α is ≥30% / ℃, which has better practical production value. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0051] Figure 1 1a is a resistance-temperature curve diagram of Examples 1-6 of the present invention; 1b is a resistance-temperature curve diagram of Comparative Examples 1-6;

[0052] Figure 2 Schematic diagram of the principle of forming a low oxygen partial pressure atmosphere of the present invention, 1 is a furnace body, 2 is a sealing flange, 3 is a gas pipeline, 4 is an oxygen pressure gauge OPP, and 5 is a mass flow controller MFC. DETAILED DESCRIPTION

[0053] The present invention will be further described with reference to the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0054] Traditional lead-containing high Curie temperature PTC ceramics are prepared by sintering in an air atmosphere, and lead-free PTC ceramic materials are usually prepared by a reduction and reoxidation process. The present invention innovatively adopts a process method for preparing lead-free high Curie temperature PTC ceramics by precisely controlling weak oxidation and low oxygen partial pressure sintering. While reducing the preparation process, a lead-free high Curie temperature PTC ceramic material with excellent comprehensive performance and greater practical value is obtained.

[0055] The PTC ceramic raw material of this application is BT-Bi 0.5 Na 0.5 TiO3 material system, the formula includes base material and auxiliary materials, the base material is BaTiO3 75-95% and Bi 0.5 Na 0.5 TiO3 5-25% weight, auxiliary materials are weighted according to the total mass percentage of TiO2 0.5-1.5%, Al2O3 0.05-0.25%, SiO2 0.5-2.5%, MnCO3 0.05-0.5%, Nb2O50.1%-0.3%, Y2O3 0.3-1.5%, CeO2 0.5-1.5%. BaTiO3 and Bi 0.5 Na 0.5 TiO3 was synthesized in the laboratory, and the remaining raw materials were purchased, with a purity of ≥99.99%.

[0056] Bi 0.5 Na 0.5 Synthesis of TiO3: Mix Na2O3, Bi2O3 and TiO2 in a 1:1:4 molar ratio in a planetary ball mill and mix them evenly. Then place them in a crucible for synthesis and sieve through 40 mesh for later use. When mixing planetary ball milling, the material: ball: anhydrous ethanol = 1:3:2, the ball milling speed is 400r / min, the ball milling time is 4 hours, and the drying temperature after ball milling is 80℃. The synthesis temperature is 1150℃, the synthesis time is 2h, and Bi is obtained. 0.5 Na 0.5 TiO3.

[0057] Synthesis of BaTiO3: Tetrabutyl titanate C 16 H 36 O4Ti and barium nitrate Ba(NO3)2 are dissolved in deionized water in a molar ratio of 1:1, stirred and ultrasonically uniformly, then transferred to a reaction kettle, sealed and kept warm at 430°C for 12 hours, cooled to room temperature, filtered, washed, dried, and sieved through 40 mesh for later use to obtain BaTiO3.

[0058] In the examples and comparative examples, different PTC raw materials were prepared according to the specified ratio, and PTC ceramic sheets were obtained through ball milling, drying, sieving, pre-sintering, crushing, granulation, molding, debinding, sintering and other processes. The PTC ceramic sheets were machined into ceramic discs with a diameter of 8 mm and a height of 3 mm, and electrodes were coated on the surface to test the RT resistance-temperature curve.

[0059] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. For ease of display, the following examples fix the ratio of each part in the auxiliary material, and are not limited to the ratio shown.

[0060] Example 1

[0061] (1) First, according to the formula molar percentage of BaTiO3 95%, Bi 0.5 Na 0.5 TiO3 5% Weigh the base material raw material, and then according to the mass percentage of the whole material BaTiO3-Bi 0.5 Na 0.5 TiO3 96.42%, TiO2 1%, Al2O3 0.1%, SiO2 1%, MnCO3 0.08%, Nb2O5 0.2%, Y2O3 0.4% and CeO2 0.8% were weighed, put into a ball mill, and anhydrous ethanol was added, wherein the mass ratio of material: ball: anhydrous ethanol was 1:3:2. After mixing for 4 hours by planetary ball mill (speed 400r / min), the raw materials were placed in an oven at 80°C for drying, sieved through 40 mesh, placed in a crucible, and pre-calculated at 900°C for 2h in a high-temperature electric furnace. After cooling to room temperature, they were crushed for later use.

[0062] (2) The pre-calcined powder was granulated with 6 wt.% PVA (polyvinyl alcohol), sieved through a 40-mesh screen, and dry-pressed on a tablet press (a pressure of 1.5 T / cm 2 , holding time 2min) to be preformed into a green billet with a diameter of 13mm and a thickness of 5mm.

[0063] (3) The PTC ceramic blank was placed in a high-temperature electric furnace and heated to 700°C at a rate of 3°C / min and kept at that temperature for 2 hours to debind.

[0064] (4) The obtained green blank after debinding is placed in Figure 2 In the atmosphere furnace body 1 shown, the sealing flanges 2 on both sides are mechanically fastened to ensure that the space inside the atmosphere furnace body 1 is sealed and leak-proof. The atmosphere furnace body 1 is externally connected to a gas pipeline 3 and a corresponding gas cylinder, a mass flow meter 5 and an oxygen pressure gauge 4. First, a certain amount of gas 1 (high-purity N2) is introduced into the gas pipeline 3, and then a certain amount of gas 2 (air) is introduced into the gas pipeline 3, and the oxygen partial pressure is adjusted to the corresponding number of the oxygen pressure gauge 4 is 700ppm.

[0065] (5) Start the heating program, first increase the temperature to 1000°C at a rate of 5°C / min, then increase the temperature to 1300°C at a rate of 7°C / min and keep it at that temperature for 45 minutes, and then cool it down to room temperature at a rate of 3°C / min.

[0066] (6) The PTC ceramics obtained above were machined into ceramic sheets with a diameter of 8 mm and a thickness of 3 mm.

[0067] (7) A layer of ohmic silver paste is screen-printed on the PTC ceramic disc, dried at 90°C, placed in a furnace and heated at 2°C / min to 500°C and kept at this temperature for 20 minutes to sinter into a metal electrode.

[0068] (8) The PTC ceramic disc with printed electrodes obtained above is placed in a resistance-temperature curve tester to test the basic parameters of related materials.

[0069] Example 2

[0070] Referring to the process flow of Example 1, the difference between this example and Example 1 is that the molar percentage of the base material formula in step (1) is BaTiO3 90%, Bi 0.5 Na 0.5 TiO3 10%; Total material mass percentage BaTiO3-Bi 0.5 Na 0.5 TiO3 96.32%, TiO2 1%, Al2O3 0.1%, SiO2 1%, MnCO3 0.08%, Nb2O5 0.3%, Y2O3 0.4%, CeO2 0.8% are weighed. In step (4), the oxygen partial pressure in the furnace is controlled to be 300ppm, and then the subsequent temperature increase program is started for sintering.

[0071] Example 3

[0072] Referring to the process flow of Example 1, the difference between this example and Example 1 is that the molar percentage of the base material formula in step (1) is BaTiO3 80%, Bi 0.5 Na 0.5 TiO3 20%; total material mass percentage BaTiO3-Bi 0.5 Na 0.5 TiO3 95.4%, TiO2 1%, Al2O3 0.1%, SiO2 0.8%, MnCO3 0.1%, Nb2O5 0.3%, Y2O3 0.8%, CeO2 1.5%. In step (4), the oxygen partial pressure of the furnace is controlled at 40ppm, and then the subsequent temperature increase program is started for sintering.

[0073] Example 4

[0074] Referring to the process flow of Example 1, the difference between this embodiment and Example 1 is that after the debinding blank is placed in the atmosphere furnace body in step (4), the atmosphere furnace is externally connected to a gas cylinder, a mass flow meter and an oxygen pressure gauge, and a N2-H2 mixed gas containing 1% H2 is first introduced, and then an appropriate amount of air is introduced into the furnace body, the oxygen partial pressure is adjusted to 700ppm, and then the temperature rise sintering program is started.

[0075] Example 5

[0076] Referring to the process flow of Example 1, the difference between this embodiment and Example 1 is that in step (4), after the debinding blank is placed in the atmosphere furnace, 200g of graphite powder is placed in the sintering furnace body, the heating program is started to heat the temperature to 600℃ at 5℃ / min and keep it warm for 10min, after the furnace body is filled with a certain amount of CO, an appropriate amount of air is introduced, the oxygen partial pressure is adjusted to 700ppm, and then the temperature is increased and sintering is carried out according to the operation of Example 1.

[0077] Example 6

[0078] Referring to the process flow of Example 1, the difference between this embodiment and Example 1 is that in step (4), high-purity nitrogen and air are introduced into the atmosphere furnace, 78 g of graphite powder is placed in the sintering furnace body, the heating program is started and the temperature is increased to 800°C at 5°C / min and kept warm for 20 minutes, so that the oxygen partial pressure in the furnace body reaches 700 ppm, and then the temperature is further increased and sintering is performed according to the steps of Example 1.

[0079] Comparative Example 1

[0080] Referring to the process flow of Example 1, the difference between this comparative example and Example 1 is that the molar percentage of the base material formula in step (1) is BaTiO3 92%, Bi 0.5 Na 0.5 TiO3 8%; total material mass percentage BaTiO3-Bi 0.5 Na 0.5 TiO3 96.42%, TiO2 1%, Al2O3 0.1%, SiO2 1%, MnCO3 0.08%, Nb2O5 0.2%, Y2O3 0.4%, CeO2 0.8%. Step (4) Control the furnace to be filled with only nitrogen, with an oxygen partial pressure of ≤10 -4 Then, the temperature was raised and sintered according to the steps of Example 1.

[0081] Comparative Example 2

[0082] Referring to the process flow of Example 2, the difference between this comparative example and Example 2 is that in step (4), the furnace is controlled to be filled with only nitrogen, and the oxygen partial pressure is ≤10 -4 ppm. Then start the temperature rise sintering program.

[0083] Comparative Example 3

[0084] Referring to the process flow of Example 3, the difference between this comparative example and Example 3 is that in step (4), only nitrogen is filled into the furnace body, and the oxygen partial pressure is controlled to be ≤10 -4 ppm. Then start the temperature rise program for sintering.

[0085] Comparative Example 4

[0086] Referring to the process flow of Comparative Example 1, nitrogen was introduced to adjust the oxygen partial pressure to ≤10 -4 ppm, the difference from Comparative Example 1 is that the heating program is started according to the operation of step (5) for sintering, and after cooling to room temperature, reoxidation treatment is carried out. The reoxidation process is carried out in an air atmosphere, the oxygen partial pressure is adjusted to 209500 ppm, the temperature is increased to 1000°C at a heating rate of 4°C / min, and the temperature is maintained for 2 hours, and then cooled with the furnace.

[0087] Comparative Example 5

[0088] Referring to the process flow of Comparative Example 1, the difference between this comparative example and Comparative Example 1 is that in step (4), a certain amount of high-purity N2 is first introduced into the atmosphere furnace, and then air is introduced into the furnace body to adjust the oxygen partial pressure to 2000ppm, and then the temperature is increased for sintering.

[0089] Comparative Example 6

[0090] Referring to the process flow of Comparative Example 1, the difference between this comparative example and Comparative Example 1 is that in step (4), only air is introduced into the atmosphere furnace body, and sintering is performed only in an air atmosphere with an oxygen partial pressure of 209500 ppm.

[0091] The experimental test data of Examples 1-6 and Comparative Examples 1-6 are shown in Table 1. The resistance-temperature curves of Examples 1-6 and Comparative Examples 1-6 are shown in Table 1. Figure 1 1a and 1b, according to Table 1 and Figure 1 By comparing the results, it can be seen that the lead-free PTC ceramic material prepared in a weakly oxidizing atmosphere and a specific low oxygen partial pressure (40-700ppm) has better comprehensive performance and better practical value than the PTC material prepared in a nitrogen reducing atmosphere or by a reduction-then-oxidation process.

[0092] Table 1 Performance parameters of PTC materials in Examples 1-6 of the present invention and Comparative Examples 1-6

[0093]

[0094]

[0095] The result of sintering in air in Comparative Example 6 is that it is not semiconductive because there are not enough carriers. The existing methods that can achieve semiconductivity in PTC material systems, i.e., sufficient carriers, are mainly doping semiconductivity and atmosphere semiconductivity. 0.5 Na 0.5 TiO3 system is highly doped with Bi 0.5 Na 0.5 TiO3 (molar percentage ≥ 4%) cannot achieve doping semiconducting of materials in air atmosphere; if it is low-doped Bi 0.5 Na 0.5 TiO3 (molar percentage <4%) can achieve doped semiconductor in air atmosphere. Therefore, in comparative example 6, due to high doping, doped semiconductor cannot be achieved, and air atmosphere cannot achieve atmosphere semiconductor, so the result is that the material cannot be semiconductor.

[0096] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a lead-free high Curie point PTC ceramic material, characterized in that: The process comprises sintering the lead-free high Curie point PTC ceramic material to be sintered in a weakly oxidizing low oxygen partial pressure atmosphere to obtain the lead-free high Curie point PTC ceramic material.

2. The preparation method according to claim 1, characterized in that: The oxygen partial pressure in the weakly oxidizing low oxygen partial pressure atmosphere is 40-700 ppm.

3. The preparation method according to claim 1, characterized in that: The sintering of the lead-free high Curie point PTC ceramic material to be sintered in a weakly oxidizing low oxygen partial pressure atmosphere specifically comprises the following steps: The lead-free high Curie point PTC ceramic material to be sintered is placed in an atmosphere furnace body, gas is introduced to form a weakly oxidizing low oxygen partial pressure atmosphere, the gas flow rate and the oxygen partial pressure of the furnace body are precisely controlled, the temperature is raised to 1240-1360°C and kept for 0.5-2h for sintering, and then the temperature is cooled to room temperature at a rate of 2-4°C / min to obtain the lead-free high Curie point PTC ceramic material.

4. The preparation method according to any one of claims 1 to 3, characterized in that: Also includes: S1. Ingredients: prepare base material and auxiliary materials. The base material is BaTiO3 75-95% and Bi 0.5 Na 0.5 TiO35-25% is weighted, and the auxiliary materials are weighted according to the total mass percentage of TiO2 0.5-1.5%, Al2O3 0.05-0.25%, SiO2 0.5-2.5%, MnCO3 0.05-0.5%, Nb2O5 0.1%-0.3%, Y2O3 0.3-1.5%, and CeO20.5-1.5% mixed with the base material; S2, PTC raw material mixing and pre-calcining: the prepared materials in S1 are mixed with anhydrous ethanol and then ball-milled, dried and sieved after ball-milling, pre-calcined, and crushed after cooling to room temperature; S3, preparing PTC green billet: adding 5-8% of the dry powder weight of organic binder to the pre-calcined and crushed PTC powder for granulation, sieving again, and molding into green billet; S4. Debinding of PTC green billet: Debinding of the green billet to obtain a lead-free high Curie point PTC ceramic material to be sintered.

5. The preparation method according to claim 4, characterized in that: The BaTiO3 in step S1 is prepared by a hydrothermal method, the preparation method comprising: 16 H 36 O4Ti and barium nitrate Ba(NO3)2 are dissolved in deionized water in a molar ratio of (0.95-1.05):1, stirred and mixed evenly, and then transferred to a reaction kettle, sealed and kept at 400-500℃ for 10-16h, cooled to room temperature, filtered, and the precipitate was washed, dried, and sieved to obtain; and / or, Bi in step S1 0.5 Na 0.5 TiO3 is prepared by a solid phase method, and the preparation method includes: mixing Na2O3, Bi2O3 and TiO2 in a molar ratio of 1:1:4 and mixing them evenly, and then synthesizing them at 1100-1200°C for 1.5-3h.

6. The preparation method according to claim 4, characterized in that: During ball milling in step S2, the mass ratio of material: ball: anhydrous ethanol is 1: (2.5-3.5): (1.5-3), the ball milling speed is 350-550r / min, and the ball milling time is 4-6h; pre-calcination is performed at 800-950°C for 1-2h.

7. The preparation method according to claim 4, characterized in that: The organic binder in step S3 is a polyvinyl alcohol solution; the molding pressure is 1-1.5T / cm 2 , maintain the pressure at this pressure for 1-3 minutes; The debinding temperature in step S4 is 500-800°C, and the debinding time is 1.5-3h.

8. The preparation method according to claim 1, characterized in that: The weakly oxidizing low oxygen partial pressure atmosphere is obtained by introducing an oxidizing gas into an inert gas or a reducing gas; or, by consuming part of the oxygen in the oxidizing gas.

9. The preparation method according to claim 8, characterized in that: The inert gas includes one or more of argon, helium, and neon; the reducing gas includes one or more of hydrogen, nitrogen, ammonia, and carbon monoxide; and the oxidizing gas includes one or more of oxygen, air, ozone, and carbon dioxide.

10. A lead-free high Curie point PTC ceramic material prepared by the method according to any one of claims 1 to 9, characterized in that: The Curie temperature T of the PTC ceramic material c 150-195℃, lift-to-drag ratio lg(R max / R min ) is 3-6, room temperature resistance R 25 The resistance is 10-1000Ω, and the resistance temperature coefficient α is ≥30% / ℃.

Citation Information

Patent Citations

  • Method for preparing high Curie point leadless PTC ceramic resistance material

    CN101224979A

  • High-temperature ceramic capacitor porcelain

    CN101417877A

  • Bi0.5Na0.5TiO3 / Ba1-xCaxTiO3-based PTC thermal sensitive ceramic material and preparation method thereof

    CN101838143A

  • Semiconductive ceramic composition

    CN1039497A

  • High use temperature lead-free PTCR (positive temperature coefficient resistance) ceramic and preparation method thereof

    CN104370539A